Meiotic spindle as a marker of optimal time for oocyte vitrification - presentation of successful infertility treatment and literature review - Mašata, Jaromír; Teplá, Olga; Jirsová, Simona; Pšeničková, Anna; Moosová, Martina; Fajmonová, Eva; Kratochvílová, Irena (Ceska gynekologie, 2024)
AIM: Within the in vitro fertilization (IVF) process, to evaluate the possibility of using the state of the meiotic spindle of oocytes as an indicator of maturity in order to optimize the timing of vitrification. PATIENTS AND METHODS: In the presented report, the cause of couple infertility was a combination of a 38-year-old female and 43-year-old male with azoospermia, which was an indication for oocyte vitrification. Oocyte polar bodies and optically birefringent meiotic spindles were visualized by polarized light microscopy and their states and relative positions were used as indicators of oocyte maturation, i.e. readiness for vitrification. Oocytes which had an angle between the polar body and meiotic spindle a ≤ 30° or had a poorly visible meiotic spindle were vitrified 4 hours post-meiotic spindle evaluation (8 hours after ovum pick-up). RESULTS: After thawing, oocytes were fully maturated and prepared for intracytoplasmic sperm injection (ICSI). Following treatment with tamoxifen, vital sperm were retrieved from the patient's partner, the oocytes were thawed and fertilized with the obtained sperm, with subsequent embryo transfer and delivery of a healthy baby at term. CONCLUSION: The meiotic spindle can be used as an oocyte maturation pointer in older women. After thawing, the oocytes were fully matured and ready for fertilization by ICSI.
Keywords: dospělí; Azoospermia; aparát dělícího vřeténka; oocyty; Humans; kryoprezervace; Cryopreservation; Spindle Apparatus; Oocytes; meiotic spindle; Vitrification; vitrifikace; mužské pohlaví; pregnancy; meióza; Adult; Meiosis; diabetes therapy in pregnancy; oocyte; fertilizace in vitro; ženské pohlaví; azoospermie; Sperm Injections, Intracytoplasmic; intracytoplazmatické injekce spermie; lidé; IVF; Male; polar body; Fertilization in Vitro; Female